Islam, Teknologi dan Pendidikan di Era Disrupsi: Penelitian - Lili Rahmawati; Jihan Muti’a Sa’ad; Febriawan Rafidi; Choky Andriano; Dwi Noviani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The era of disruption, marked by rapid technological development, has brought fundamental changes in various aspects of life, including education. Islamic education, as a system with a long tradition in the transmission of knowledge and religious values, faces significant challenges in adapting to this new reality. This journal aims to analyze the impact of technology on Islamic education, identify the challenges and opportunities that arise in the era of disruption, and offer solutions to reformulate Islamic education to remain relevant and effective.